Public policy, school reform, and special education : a practical guide for every teacher - Ysseldyke, James E.; Algozzine, Robert (Practical approach to special education for every teacher, 2006)
Case studies illustrate how social, political, and economic factors affect special education practices and the distribution of limited resources to students with special needs.